Pengaruh Literasi Keuangan, Persepsi Kemudahan Penggunaan Dan Risiko Terhadap Minat Menggunakan E-Wallet Masyarakat Palembang - Barkiah Syafitri; Andrian Noviardy (Ikatan Da'i Indonesia, 2025)
This study aims to examine the influence of financial literacy, perceived ease of use, and perceived risk on the interest in using e-wallets among the people of Palembang. With the rapid growth of digital financial technology, e-wallet usage has become increasingly popular. However, factors such as users' financial knowledge, the simplicity of technology, and concerns about potential risks may affect their intention to adopt this payment method. The research employed a quantitative approach by distributing questionnaires to a sample of Palembang residents. Data were analyzed using statistical methods to determine the relationship between these variables and e-wallet usage interest. The results indicate that financial literacy and perceived ease of use have a positive and significant effect on the interest in using e-wallets, while perceived risk has a negative impact. The findings highlight the importance of increasing financial education and improving user-friendly features to encourage wider adoption of e-wallets in Palembang.